Religious studies of cannibalism - Serhiy Titov (Cхід, 2017)
The article provides a comprehensive review of latest religious studies research into the phenomenon of cannibalism. All materials are supported with real-world modern examples, based on media reports and findings of primatology and anthropology. In attempt of revealing religious aspect of cannibalism the article presents interesting findings from the author's own anthropological experience in Western Africa. Using classification schemes of the subject, mainly developed and represented in the field of anthropology, the author compares similar aspects in both approaches of anthropology and religious studies. Having applied a variety of classification schemes and methods, the author demonstrates a number of interesting findings.